Advanced registration tools for XFM - Durmaz, Fevzi Aytaç. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2010., 2010)
Minimally invasive therapies are very common in today's healthcare. Many procedures which require invasive surgery, with its associated long recovery times and high cost, can now be performed more e ectively, with less trauma to the patient, by using smaller incisions and specialized surgical instruments. During interventional studies X-ray Angiography provides us with high resolution images at su cient frame rate, but it doesn't have the desired soft tissue contrast. MR imaging on the other hand provide 3-D anatomic imaging with excellent soft tissue contrast. Our aim is to fuse 2-D X-ray images with a priori 3-D MR volumes during medical interventions to assist physicians. X-ray fused with MRI (XFM) is an approach which combines strengths of both image modalities to improve the quality of image-guidance during minimally invasive interventions. In XFM, pre-operative MR images are segmented, 3D structure of target area is reconstructed from these segments, and after registration its projection is overlapped on top of live images during X-ray uoroscopy. Fusion of two modalities requires registration which could be achieved by using several algorithms. In this study we are using an intensity based 2D-3D registration algorithm rigid, multimodality intrasubject registration using mutual information between two modalities. The results of intensity based algorithm is compared with ducial based registration results for the same datasets. Our preliminary results show that our method has the potential to locate the MR image on top of 2D X-ray image with high accuracy in fusing both modalities.|Keywords: Image-Guided Medical Intervention, X-ray Fused with MRI (XFM), Intensity Based Image Registration, Hybrid (MRI X-ray) Imaging Systems.
Keywords: Image registration.; Magnetic resonance imaging.